Modern methodology of organizing career guidance (Gumilyov Journal of Pedagogy, 2026)
The article discusses the relevance of conducting career guidance work in secondary schools, the importance of organizing it on the basis of an atlas of new professions and competencies. In the conditions of the actively changing modern world, the labor market is also changing rapidly. While some professions appear and become increasingly popular, others are becoming less popular and are beginning to be forgotten. Therefore, the question arises: «What profession is better to master?» A prestigious profession attracts many people and is highly competitive, both when entering school and when getting a job. Therefore, in order to achieve high income and career success, an applicant must be prepared for difficult tests and great competition. The applicant has the opportunity to choose professions that are in demand today and in the future with the help of an atlas of new professions. An atlas of new professions and competencies is a collection of professions that, according to experts in various fields, are already in demand and will appear in the near future. This atlas provides us with a list of professions that will be in great demand in the near future, within 5-10 years. The article presents a description of several new professions proposed in this atlas. In addition, the results of an experiment conducted to determine the aptitude of 9th-grade students of 2 secondary schools in Astana are presented.